A LEGAL ANALYSIS ON FOOD SECURITY UNDER INTERNATIONAL ENVIRONMENTAL LAW - Amalia Zuhra (Masalah-Masalah Hukum, 2014)
Food security is a global issue and a concern of the international community . Food security is related to many aspects, such as economic, social , cultural , and environmental . Linkages with food security and environmental sustainability are closely inseparable . Balanced environment will help achieve sustainable food security . On the other hand , efforts to achieve food security must be environmentally sustainable . International environmental law governing food security in several instruments both " hard law" or " soft law " . Implementation of the present international environmental law can help to achieve sustainable food security. Keywords : Food Security, Agriculture, International Environmental Law. Ketahanan pangan merupakan permasalahan global dan menjadi perhatian masyarakat internasional. Ketahanan pangan terkait dengan banyak aspek di dalamnya, seperti ekonomi, sosial, budaya, dan lingkungan. Keterkaitan ketahanan pangan dengan kelestarian lingkungan sangat erat dan tidak terpisahkan. Lingkungan yang seimbang akan membantu tercapainya ketahanan pangan yang lestari. Di lain pihak, upaya pencapaian ketahanan pangan harus memperhatikan kelestarian lingkungan. Hukum lingkungan internasional  mengatur tentang ketahanan pangan dalam beberapa instrumen baik yang bersifat “hard law” maupun “soft law”. Pengimplementasian hukum lingkungan inetrnasional dapat membantu tercapainya ketahanan pangan yang lestari.   Kata kunci: Ketahanan Pangan , Pertanian , Hukum Lingkungan Internasional